2020
DOI: 10.1002/acp.3626
|View full text |Cite
|
Sign up to set email alerts
|

“Who said it?” How contextual information influences perceived profundity of meaningful quotes and pseudo‐profound bullshit

Abstract: Summary Psychological research on pseudo‐profound bullshit—randomly assembled buzz words plugged into a syntactic structure—has only recently begun. Most such research has focused on dispositional traits, such as thinking styles or political orientation. However, none has investigated contextual factors. In two studies, we introduce a new paradigm by investigating the contextual effect on pseudo‐profound bullshit and meaningful quotes. In Study 1, all participants rated the profundity of statements in three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
3
15
1
1
Order By: Relevance
“…While this approach makes it more difficult to single out which specific factor contributes to the source effect, it increases the ecological validity of our manipulation: real life instances of source credibility also involve a combination of different features (e.g., authorities typically look the part in public and appear in congruous contexts). Furthermore, a recent study showed that the mere mentioning of a famous source such as Aristotle or the Dalai Lama enhanced profundity ratings for pseudo-profound nonsense relative to unauthored versions, suggesting that even the mere name of an authority may suffice to induce source effects 87 .…”
Section: Discussionmentioning
confidence: 99%
“…While this approach makes it more difficult to single out which specific factor contributes to the source effect, it increases the ecological validity of our manipulation: real life instances of source credibility also involve a combination of different features (e.g., authorities typically look the part in public and appear in congruous contexts). Furthermore, a recent study showed that the mere mentioning of a famous source such as Aristotle or the Dalai Lama enhanced profundity ratings for pseudo-profound nonsense relative to unauthored versions, suggesting that even the mere name of an authority may suffice to induce source effects 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, very similar context effects were registered with bullshit. When attributed to an author who is famous , or implemented in a vignette or an authored excerpt from a book, bullshit is deemed more profound than when presented isolated (Gligorić & Vilotijević, 2019). The authors call this effect of varying bullshit context “the labeling effect” (Gligorić & Vilotijević, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When attributed to an author who is famous , or implemented in a vignette or an authored excerpt from a book, bullshit is deemed more profound than when presented isolated (Gligorić & Vilotijević, 2019). The authors call this effect of varying bullshit context “the labeling effect” (Gligorić & Vilotijević, 2019). Although this finding gives very valuable insight into the fact that the context in which people encounter bullshit influences their judgment about bullshit, it does not provide information about what is it about the ascribed authors that drives the changes in profoundness evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…U skladu sa time i malobrojna istraživanja kontekstualnih faktora koji utiču na receptivnost na verbalizme upravo su se ticala izvora iskaza tj. uticaja pripisanog autorstva na receptivnost na PDV (na primer Gligorić & Vilotijević 2019;Ilić 2019;. Ipak, sama ideja o uticaju izvora na procene dubokoumnosti nije revolucionarni izum autora ovih istraživanja već potiče još iz Penikukovog početnog istraživanja ovog fenomena (Pennycook et al 2015), a tiče se epistemički inferiorne pozicije ispitanika u psihološkom istraživanju.…”
Section: Istraživanja Kontekstualnih Faktora Koji Utiču Na Receptivnounclassified